Cooperative work and coordinative practices contributions to the conceptual foundations of computer-supported cooperative work (CSCW) - Schmidt, Kjeld (Computer supported cooperative work, 2011)
The development of computing technologies have from the very beginning been tightly interwoven with the development of cooperative work, but over the last couple of decades, computing technologies are increasingly being developed and used for coordinative purposes, as a means of regulating complex activities involving multiple professional actors, in factories and hospitals, in pharmaceutical laboratories and architectural offices, and so on. The economic importance of the applications of these coordination technologies is enormous but their design often inadequate. The problem is that our understanding of the coordinative practices, for which these coordination technologies are being developed, is quite deficient, leaving systems designers and software engineers to base their system designs on rudimentary technologies. The research reflected in this book addresses these very problems. The book contains a series of articles that has played an important role in establishing the conceptual foundations of the research area of Computer-Supported Cooperative Work (CSCW). These articles are complemented by four new chapters in which CSCW's research program is subjected to critical examination and clarification.